Primary Caregivers Health Seeking Behaviour for Under-Five Children: A Study in a Rural Block of Assam, India - Kalita, Debadeep; Borah, Madhur; Kakati, Rana; Borah, Hiyeswar (National Journal of Community Medicine, 2016)
Introduction: Proper health seeking behaviour of primary caregivers can reduce delay in diagnosis of illness of young children, improve treatment compliance, improve the health, reduce child mortality and morbidity. The present study was conducted with the objectives to study the prevailing health seeking behaviours of care givers for the under five children. Methodology: Total 375 primary caregivers of under 5 children were included in our study. Each caregiver was interviewed after taking informed consent using pretested predesigned semi structured schedule. Results: Out of 283 episodes in 31% cases the caregiver approach govt hospital while 23.7% went to private clinics, 17% practiced self medication for the child. 16% primary caregivers sought no outside advice and 5% went to traditional healers. Lack of money was cited by 75% caregivers as the reason for not getting outside treatment while 84% caregivers felt that the morbidity episode of the child was not sever enough to seek care. Conclusion: The study findings includes government sector is still the preferred choice for rural population for treatment for their children, self medication practices were forced on children by some caregivers, education of the caregivers significantly influenced care seeking behaviour, lack of money and caregivers’ perception of mild illness were some reasons for not seeking appropriate care.